2009
DOI: 10.1111/j.1747-1346.2007.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

2 > 1 + 1? The Impact of Contact with Gay and Lesbian Couples on Attitudes about Gays/Lesbians and Gay‐Related Policies

Abstract: Contact with individual lesbians and gay men leads to more positive evaluations of the group and more support for pro-LGBT (lesbian, gay, bisexual, and transgender) public policies. Increasingly, gay rights activists are making "gay families" central to their communications to the public about gay issues and policies. This prompts a new question in the area of contact theory: does contact with same-sex couples have a different impact on attitudes about gays/lesbians and gay-related public policies than conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 12 publications
0
30
1
1
Order By: Relevance
“…Reasons for this liberalization include demographic shifts, more positive media portrayals of gays and lesbians, changing beliefs about the nature of homosexuality, and more frequent personal contact with gays and lesbians . Personal contact with gays or lesbians is associated with lower levels of prejudice (Herek and Capitanio, 1996;Lance, 1987;Smith et al, 2009) and greater support for gay rights Lewis and Gossett, 2008;Barth and Parry, 2009;Lewis, 2011). In fact, in their comparison of intergroup contact effects across various societal subgroups, Pettigrew and Tropp (2006) report that the largest effects stem from contact between heterosexuals and gay men or lesbians.…”
Section: Contact With Gays and Lesbiansmentioning
confidence: 90%
“…Reasons for this liberalization include demographic shifts, more positive media portrayals of gays and lesbians, changing beliefs about the nature of homosexuality, and more frequent personal contact with gays and lesbians . Personal contact with gays or lesbians is associated with lower levels of prejudice (Herek and Capitanio, 1996;Lance, 1987;Smith et al, 2009) and greater support for gay rights Lewis and Gossett, 2008;Barth and Parry, 2009;Lewis, 2011). In fact, in their comparison of intergroup contact effects across various societal subgroups, Pettigrew and Tropp (2006) report that the largest effects stem from contact between heterosexuals and gay men or lesbians.…”
Section: Contact With Gays and Lesbiansmentioning
confidence: 90%
“…This is not meant to downplay the significance that such a policy change would have for countless gay and lesbian couples who seek to marry, but rather a political strategy geared toward those who have not yet formed their opinion about same-sex marriage. Campaigns that highlight personal stories about the importance of same-sex marriage to real-life same-sex couples have been shown to demonstrate positive results in this regard (Barth and Parry 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, although contact with people who are LGBQ or same-sex couples had a significant impact on attitudes towards same-sex marriage in general and legalizing same-sex relations (Tables 3 and 6), it did not affect attitudes towards same-sex adoption. A variation in impact with LGBQ individuals and same-sex couples on attitudes towards different types of same-sex-headed families was also evident in the work of Barth and Parry (2009), who determined that same-sex couples had more impact on attitudes towards same-sex marriage, whereas simply knowing someone who is lesbian or gay better predicted attitudes towards same-sex adoption.…”
Section: Impact Of Types Of Contactmentioning
confidence: 94%
“…Barth and J. Parry (2009) expanded on this line of research by testing whether knowing someone in a same-sex romantic relationship had greater impact on attitudes than simply knowing someone who identified as gay or lesbian. They concluded that knowing same-sex couples had a distinct impact on attitudes towards legal recognition of same-sex partnerships; however, knowing a lesbian or gay man, whether in couples or not, was a stronger predictor of support in regard to other policies (e.g., nondiscrimination laws, adoption of children by lesbians and gay men; Barth and Parry 2009).…”
Section: The Contact Hypothesis and Influence On Attitudesmentioning
confidence: 99%